Sosialisasi Dan Edukasi Publik Pasar Modal Di SMA Negeri 5 Bengkalis Provinsi Riau - Fakhruddin, Imam; Firdaus, Firdaus; Lena Mardiany; Nur Alisa (Jurnal Pengabdian UntukMu NegeRI, 2024)
The current problem is that many schools do not provide financial knowledge to their students. Students must learn about early investment in accordance with technological and scientific developments. Therefore, many students do not understand investment and capital markets, so they do not have the enthusiasm to save for the future. The aim of this program is to improve the knowledge of students about investment in the capital market and reduce the impact of low interest in investing in capital markets. Furthermore, the purpose of this dedication is to provide education and training on investment in a capital market to students of SMA Negeri 5 Bengkalis.